1993
DOI: 10.1007/bf00232312
|View full text |Cite
|
Sign up to set email alerts
|

Production of cucumber fruits from the culture of ?Marketmore-76? plantlets

Abstract: A procedure to produce fruits from cultured shoot tips of Cucumis sativus L. cultivar 'Marketmore-76' in vitro is described. Four-week-old shoot tips, derived from sterile germinated seedlings on a MS medium, were cultured in a 3.8-1 Mason jar using an automated plant culture system. Tips readily generated roots, leaves and flowers after another 4 to 8 weeks in culture. Administration of compressed air at a 300 ml/min flow rate for 30 min 10 or 15 times a day induced the development of parthenocarpic fruits fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
10
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 4 publications
1
10
0
Order By: Relevance
“…In this study, considerably larger vessels and medium volumes were employed and they enhanced flowering and culture growth. In prior studies, Tisserat & Galletta (1993;1995) found that an APCS employing large culture chambers (e.g.  ½-gallon Mason jars) allowed for flowering and fruiting from cucumbers and pepper plantlets.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In this study, considerably larger vessels and medium volumes were employed and they enhanced flowering and culture growth. In prior studies, Tisserat & Galletta (1993;1995) found that an APCS employing large culture chambers (e.g.  ½-gallon Mason jars) allowed for flowering and fruiting from cucumbers and pepper plantlets.…”
Section: Resultsmentioning
confidence: 99%
“…In prior studies, the production of fruits from flowers in vitro was achieved with a great degree of cultural manipulation (AlJuboory et al, 1991;Dickens & Van Staden 1985;1988;Ishioka et al, 1991;Pasqua et al, 1991;Rastogi & Sawhney 1986;Tisserat & Galletta 1993;1995). This study will investigate a number of the parameters which have been identified as considered important factors to promote flowering and fruiting reports.…”
mentioning
confidence: 99%
See 3 more Smart Citations